The Effects of Maternity Leave Benefits on Mothers and Children. A Reexamination - Otto Sevaldson Lillebø; Simen Markussen; Knut Røed (Institute of Labor Economics (IZA), 2025)
We provide a full reexamination of the effects of a maternity leave extension implemented in Norway in 1977. Previous research reporting large favorable long-term effects on mothers' health and on offspring's educational and labor market outcomes relied on an incorrect description of the reform and an invalid identification strategy. In the present paper, we show that the previously reported results are misleading. Building on an accurate description of the reform and its implementation, we document that it had no noticeable long-term effects on mothers' health or on offspring's education and labor market outcomes.
Keywords: C52; J13; J18; 330; family policies; maternity leave; replication